Testing for Neglected Nonlinearity in Weekly Foreign Exchange Rates - Sadique, Shibley (Academic Research Council, 2011)
This study investigates the presence of neglected nonlinearity in weekly exchange rates of five countries in terms of Australian dollar. Three prominent nonlinear models from the ARCH family, such as the EGARCH, GARCH-M and EGARCH-M are fitted to the first differenced log of exchange rate series. The logs of the squared standardized residuals from the fitted models are tested for any leftover nonlinear structure using the BDS test. The nature of the leftover nonlinear dependence is identified using the Odd Product Moment Test of Hsieh (1991). Overall, the empirical evidence obtained in this study support the claim that the ARCH-type models cannot capture all the nonlinearities in financial asset returns.